Pengaruh Metode Bil Qolam dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di SMP Khadijah Surabaya - Ningsih, Dessi Fitria (LPPM Institut Pendidikan Nusantara Global, 2024)
The use of the bil qolam method applied at Khadijah Middle School in Surabaya is very important to study because this method is effective and has been proven to be able to produce a generation that is able to read the Al-Qur'an. The research method uses a quantitative approach, using percentage analysis techniques and Pearson product moment correlation. The population in this study were students in grades IX-X-XII, totaling 439 students. The sampling technique in this research used the Quota Porposive Random Sampling technique which was taken randomly from 439 students so that 20% was taken, namely 439 x 20%, namely 88. For data collection, questionnaires, observation and documentation were used. The location of this research is Khadijah Middle School, Surabaya. The results of the research show that the use of the bil qolam method at Khadijah Middle School Surabaya is in the very good category, namely reaching 89.20% which is in the 80%-100% interval. Meanwhile, the ability to read the Al-Qur'an at Khadijah Middle School Surabaya is categorized as very good, reaching 91.25%, which is in the 80%-100% interval. And there is an influence between the bil qolam method on the ability to read the Al-Qur'an of Khadijah Surabaya Middle School students, this is proven in the product moment analysis with a value of rxy = 0.603 which is included in the correlation coefficient interval of 0.60-0.799 which is classified as having a strong influence. There is a significant influence between the bil qolam method on students' ability to read the Al-Qur'an at Khadijah Middle School Surabaya, this is proven by tcount > ttable, namely 0.0097 > 1.66623.